Transition to motherhood: The role of health - Irina Simankova; Harald Tauchmann (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2024)
The age at which women become mothers for the first time is ever increasing in many industrialized countries. Therefore, fertility determinants that might deteriorate with age, such as health, and their effect on reproductive patterns, should be given more attention. We explore the effect of the subjective general health of women of reproductive age on the conditional probability of entering motherhood. Based on estimating linear discrete-time hazard models using survey data from Germany, we do not find a homogeneous health effect on the probability of having a first child. However, allowing effect heterogeneity over the span of reproductive age reveals that the role of health is ambiguous. While good health is associated with a lower probability of entering motherhood at the beginning of the reproductive phase, the opposite holds for the late reproductive phase. This pattern is robust to employing different estimation methods (parametric, non-parametric), conditioning on socio-economic characteristics, and taking unobserved individual-level heterogeneity into account.
Keywords: C41; I19; J13; 330; motherhood; fertility; discrete-time survival analysis; instrumental variables estimation